Pengaruh Displin Kerja dan Motivasi Kerja terhadap Kinerja Pegawai pada Direktorat Jenderal Cipta Karya Kementerian Pekerjaan Umum - Ilham, Muhammad; Muhtadin, Imam (Universitas Islam Kadiri, 2025)
This study examines the influence of work discipline and work motivation on employee performance at the Directorate General of Cipta Karya, Ministry of Public Works. The research aims to determine the extent to which these two factors contribute to employee performance. A quantitative associative research approach was used, with primary and secondary data collected through questionnaires distributed to 50 respondents. The study employed a saturated sampling technique, ensuring that all members of the population participated. Data analysis was conducted using multiple linear regression, including validity and reliability tests, classical assumption tests, and hypothesis testing (t-test and F-test). The findings indicate that work discipline and work motivation both have a positive and significant impact on employee performance, both individually and simultaneously. The coefficient of determination (R²) shows that 97% of employee performance is influenced by these two factors, while the remaining 3% is affected by other variables. These results highlight the importance of maintaining high discipline and motivation to optimize employee performance and contribute to organizational success.